Music-guided resonance breathing – An exploratory sequential mixed-methods study for development and testing of a music intervention for pre- or perioperative stress reduction - Metzner, Susanne; Fuchs, Dominik; von der Nahmer, Peter Michael (The Arts in psychotherapy, 2024)
Music-Guided Resonance Breathing (MGRB) is a combination of a technique for consciously slowed breathing and attentive music listening in health care contexts. MGRB is intended for clinical application to reduce anxiety and stress in patients undergoing strenuous medical treatment. The article sets out the basic principles and effects of resonance breathing and describes the development process of MGRB in form of an exploratory sequential mixed-methods study. Music therapy experts, healthy subjects and a professional composer have contributed to the research, aiming to understand the optimal musical characteristics of MGRB and anticipating feasibility as well as effects on the psychological and physical states of future patients. The results encourage to conduct a controlled clinical trial with MGRB. •Music-guided resonance breathing is for patients undergoing stress-inducing medical treatment.•The characteristics of music and the psychophysical processes are both decisive for the effectiveness.•The development of a music intervention requires an exploratory mixed-methos research design.